Glory of the Kushans : recent discoveries and interpretations - Kushan Glory and Its Contemporary Challenges (Seminar) (2008 : Bharat Kala Bhavan, Banaras Hindu University); Jayaswal, Vidula, 1947- (New Delhi : Aryan Books International, 2012)
"This volume is an outcome of the International Seminar entitled, 'Kushan Glory and Its Contemporary Challenges', which was organized by the Bharat Kala Bhavan, Banaras Hindu University, Varanasi (India), between October 3 and 5, 2008" (p. ix).
Includes bibliographical references (pages 393-442) and index.
Keywords: Kushans -- India -- History -- Congresses; India -- History -- 324 B.C.-1000 A.D. -- Congresses; India -- Civilization -- To 1200 -- Congresses